Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium

Optimization of the anti-cancer activity of the phosphatidylinositol-3 kinase pathway inhibitor PITENIN-1: switching thiourea with 1,2,3-triazole - Kommagalla, Yadagiri; Cornea, Sinziana; Riehle, Robert; Torchilin, Vladimir; Degterev, Alexei; Ramana, Chepuri V. (Medchemcomm, 2014)
We previously reported encouraging in vitro and in vivo anti-cancer activity of N-((3-chloro-2-hydroxy-5-nitrophenyl)carbamothioyl) benzamide (termed PITENIN-1). In the current work, we describe the structure-activity relationship study of the PIT-1 series, based on the replacement of a central thiourea unit with 1,2,3-triazole, which leads to increased liver microsomal stability, drug likeness and toxicity towards cancer cells.

Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium

Ruthenium(II)-catalyzed switchable C3-alkylation versus alkenylation with acrylates of 2-pyridylbenzofurans via C-H bond activation - Kommagalla, Yadagiri; Mullapudi, Venkanna Babu; Francis, Fredi; Ramana, Chepuri V. (Catalysis Science & Technology, 2015)
We documented an interesting observation of ruthenium (II)-catalyzed benzofuran C-H activation and subsequent functionalization with acrylates that reveals that a simple base can switch the process from alkylation to alkenylation.

Re-engineering of PIP3-antagonist triazole PITENIN's chemical scaffold: development of novel antifungal leads - Pulya, Sravani; Kommagalla, Yadagiri; Sant, Duhita G.; Jorwekar, Shweta U.; Tupe, Santosh G.; Deshpande, Mukund V.; Ramana, Chepuri V. (RSC Advances, 2016)
A novel 4-(1-phenyl-1-hydroxyethyl)-1-(o-hydroxyphenyl)-1H-1,2,3-triazole was designed by integrating the structural features of triazole PITENIN anticancer agents and the azole class of antifungal drugs. A two-step protocol comprising the Barbier propargylation and Cu-catalyzed azide-alkyne cycloaddition was established to synthesise a diverse set of compounds of this class. Their screening against a wide range of human fungal pathogens led to identification of several potential antifungal hits and some of them displayed better antifungal activity than fluconazole against Candida glabrata, Cryptococcus neoformans, Aspergillus fumigatus and Aspergillus niger. Mode of action studies revealed that their antifungal activity was resulting either from the inhibition of lanosterol 14 alpha-demethylase enzyme (leading to ergosterol depletion) or by the generation of reactive oxygen species (ROS).

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations